2021
DOI: 10.3126/jnps.v41i2.31151
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Expressed Breast Milk Awareness Among Mothers in Siddharthnagar Municipality of Rupandehi District, Nepal

Abstract: Introduction: Expressed breast milk is the practice of squeezing breast milk for the purpose of further use. Infant and young child feeding is very important in promoting healthy growth and development, particularly during the first two years of child’s life. The awareness of mothers regarding expressed breast milk has a direct impact on the life of infants and feeding practices. The study aimed to find out possible determinants of awareness regarding expressed breast milk among mothers. Methods: Descriptive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Mother's age had the highest regression effect on the child's defecation control skill, and parental self-efficacy was placed in the next rank. The results of Shrooti et al (29) and Bhattarai and Bhusal (32) study were in line with the results of the present study, and Alie et al showed that there was an inverse significant relationship between the mother's self-efficacy and the mother's age (28). It can be explained that younger parents are more motivated to learn and can have positive control over children's behavioral problems by believing in themselves.…”
Section: Resultssupporting
confidence: 92%
“…Mother's age had the highest regression effect on the child's defecation control skill, and parental self-efficacy was placed in the next rank. The results of Shrooti et al (29) and Bhattarai and Bhusal (32) study were in line with the results of the present study, and Alie et al showed that there was an inverse significant relationship between the mother's self-efficacy and the mother's age (28). It can be explained that younger parents are more motivated to learn and can have positive control over children's behavioral problems by believing in themselves.…”
Section: Resultssupporting
confidence: 92%